Magnesium and Zinc Intake Ratio Mediates the Increase of Coronary Artery Calcification through Upregulating Interleukin 6. Issue 1 (31st December 2022) - Al-Qaridhi, Abdulhakim; Ghosh, Sounak; Luo, Dongling; Huang, Hui
ABSTRACT: The relation between dietary minerals and coronary artery calcification (CAC) has been emphasized. However, the effects of multiple dietary minerals on CAC progression remain unclear. This study Investiagetes the effect of combined dietary mineral intake on the progression of CAC. We analyzed a population-based cohort with 6814 participants from the Multi-Ethnic Study of Atherosclerosis (MESA). CAC scores were measured at baseline and subsequent follow-up examinations by Multi-detector computed tomography (MDCT) scans with Agatston scores. Then, the progression of CAC was defined through increased CAC scores in the follow-up from the baseline exam. The results revealed that the dietary intake of individual minerals did not show significant differences across CAC progression vs non progression groups. However, participants with CAC progression had an increased Magnesium (Mg):Zinc (Zn) ratio ( P < 0.05). This effect was significant in logistic regression after adjusting for multiple established risk factors of CAC progression (OR 1.050; 95% CI 1.003, 1.099; P = 0.038). The increased risk of CAC associated with Mg/Zn was mediated through an increase level of IL-6, which increased with association to the Mg: Zn ratio. In conclusion, the dietary of Mg: Zn ratio, rather than individual mineral intake is associated with increased risk of CAC progression, which is mediated by pro-calcific IL-6. Therefore, the consideration of dietary intake of Zn and Mg together would play a cardio protective role among CAC patients.